Relationship between ionized calcium and serum albumin level in children with idiopathic nephrotic syndrome - Viiola Irene Winata; Dida Akhmad Gurnida; Nanan Sekarwana (Indonesian Pediatric Society, 2010)
Background Nephrotic syndrome (NS) patients frequently have abnormalities in calcium metabolism that manifest as hypocalcemia and reduced intestinal absorption of calcium. Hypocalcemia is initially attributed to hypoalbuminemia but it may also relate to a low level of ionized calcium. The ionized calcium level depends on the severity and duration of proteinuria.Objective To assess the rel ationship between ionized calcium and serum albumin level in idiopathic NS children.Methods An analytical study with cross-sectional design was applied to NS and healthy children between 1-14 years old in the Child Health Department of Hasan Sadikin Hospital, Bandung from December 2009 to April 2010. Ionized calcium was examined by Ca2 + analyzer AVL 980 with ion-selective electrodes (ISE) methods.Results A total of34 subjects were recruited, consist of 17 NS and 17 healthy children. The mean ionized calcium and serum albumin level in NS children was 4.56 (SD 0.23) mg/dLand 1.45 (SD 0.24) g/dL, respectively. Statistical difference between ionized calcium level in NS and in healthy children was significant (P<0.05). Pearson correlation test between ionized calcium and serum albumin was significant (P<0.05) with correlation coefficient (r) 0.53. We found the following equation to estimate ionized calcium (y) based on the serum albumin level (x): y=3.84+0.49x.Conclusion There is a moderately positive linear relationship between ionized calcium and serum albumin level in NS children.